Efforts To Increase Regional Original Income Through The Kelurahan Parking Service System Mount Sari City Makassar - Andi Arifwangsa Adiningrat; Arniati Arniati; Wahyu Nirmala Sinta; Warda Warda (Universitas Muhammadiyah Makassar, 2022)
The purpose of this study was to determine the implementation of the parking service system in Gunung Sari Village in increasing the local revenue of Makassar City, the research method used was qualitative with an objective description of the state of the parking service system, and the type of research used was descriptive qualitative that revealed facts. about the parking service system. The data sources used are primary and secondary data sources and the number of informants is 6 people. Data collection techniques using the method of Observation, Interview, Documentation and Literature Study. The data analysis techniques used are reducation, data display, and conclusion drawing/verification. The results of this study indicate that the existence of a parking service system managed by PD Parking Makassar Raya can help people park their vehicles in Makassar City. This parking service system service can also help increase Makassar City's Regional Original Revenue until the target set is achieved